2018
DOI: 10.1177/0017896917752014
|View full text |Cite
|
Sign up to set email alerts
|

Children’s healthy eating habits and parents’ socio-demographic characteristics in rural Texas, USA

Abstract: Objective: Due to the disproportionately high rates of obesity within the US Hispanic community, there is a critical need to address this health disparity issue. The aim of this study is to examine the relationship between parents’ socio-demographic characteristics and their children’s food consumption. Design: Cross-sectional study. Setting: Participants were recruited from schools in a predominately Hispanic rural area of Texas, USA. Method: Parents ( n = 298) of fourth grade (9–10 years old) children comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
0
12
1
Order By: Relevance
“…Our differential findings by race/ethnicity favouring White students who showed larger increases in overall healthy eating score over time, did not hold true between other racial/ethnic groups. While racial and ethnic differences in intake and self-efficacy among adolescents have been shown, it may be that this relationship does not quite exist as strongly in children as our results have shown to some degree, or that SES may be the driving force in creating differences, rather than race/ethnicity (Chen et al, 2018;Fahlman et al, 2010), which we were unable to measure in this study. We did not find racial/ethnic differences in individual food groups.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Our differential findings by race/ethnicity favouring White students who showed larger increases in overall healthy eating score over time, did not hold true between other racial/ethnic groups. While racial and ethnic differences in intake and self-efficacy among adolescents have been shown, it may be that this relationship does not quite exist as strongly in children as our results have shown to some degree, or that SES may be the driving force in creating differences, rather than race/ethnicity (Chen et al, 2018;Fahlman et al, 2010), which we were unable to measure in this study. We did not find racial/ethnic differences in individual food groups.…”
Section: Discussioncontrasting
confidence: 66%
“…Furthermore, Fahlman (2010) and colleagues found that Black adolescents (mean age 12-13 years) of lower socioeconomic status (SES) scored worse in dietary behaviours, knowledge and self-efficacy than their White adolescent counterparts (Fahlman et al, 2010). From a rural sample of children aged 9-10 years and parents in Texas, researchers found that children's healthy eating can be predicted by parent's gender, race/ethnicity, education and income (Chen et al, 2018), such that higher income and more educated parents have children who eat less healthy. Even so, in their study, ethnicity was the strongest predictor of healthy eating.…”
Section: Introductionmentioning
confidence: 99%
“…Preventive health behaviors refer to any activity undertaken by an individual who believes himself or herself to be healthy for the purpose of preventing disease [6]. For example, children living in rural areas consume less fruit and vegetable than their urban peers [7]; rural residents were less likely to wear sunscreen to prevent skin cancer than urban residents [8]; and women living in rural locations were less likely to receive mammography and Papanicolaou (Pap) smear screening to prevent cervical and breast cancer than their urban counterparts [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition interventions focusing on school settings and the involvement of parents may bring positive changes in children's dietary behaviour, subsequently reducing the prevalence of childhood obesity (Chen et al, 2018;McHugh et al, 2019;Sahoo et al, 2015). Two recent systematic reviews recommended that interventions that focus on behaviour-specific nutrition education lessons, hands-on activities, and reinforcement are more successful in promoting healthy behaviour than interventions not including these components (Hendrie et al, 2017;Murimi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%